Smoking cessation in European patients with coronary heart disease. Results from the EUROASPIRE IV survey: A registry from the European Society of Cardiology. (1st May 2018) - Snaterse, M.; Deckers, J.W.; Lenzen, M.J.; Jorstad, H.T.; De Bacquer, D.; Peters, R.J.G.; Jennings, C.; Kotseva, K.; Scholte op Reimer, W.J.M.; ,
Abstract: Objective: We investigated smoking cessation rates in coronary heart disease (CHD) patients throughout Europe; current and as compared to earlier EUROASPIRE surveys, and we studied characteristics of successful quitters. Methods: Analyses were done on 7998 patients from the EUROASPIRE-IV survey admitted for myocardial infarction, unstable angina and coronary revascularisation. Self-reported smoking status was validated by measuring carbon monoxide in exhaled air. Results: Thirty-one percent of the patients reported being a smoker in the month preceding hospital admission for the recruiting event, varying from 15% in centres from Finland to 57% from centres in Cyprus. Smoking rates at the interview were also highly variable, ranging from 7% to 28%. The proportion of successful quitters was relatively low in centres with a low number of pre- event smokers. Overall, successful smoking cessation was associated with increasing age (OR 1.50; 95% CI 1.09–2.06) and higher levels of education (OR 1.38; 95% CI 1.08–1.75). Successful quitters more frequently reported that they had been advised (56% vs. 47%, p < .001) and to attend (81% vs. 75%, p < .01) a cardiac rehabilitation programme. Conclusion: Our study shows wide variation in cessation rates in a large contemporary European survey of CHD patients. Therefore, smoking cessation rates in patients with a CHD event should be interpreted in the light of pre-event smoking prevalence, and caution is needed when comparing cessation rates across Europe. Furthermore, we found that successful quitters reported more actions to make healthy lifestyle changes, including participating in a cardiac rehabilitation programme, as compared with persistent smokers. Highlights: Across EUROASPIRE II–IV survey cohorts, the smoking cessation percentage remained unchanged. Smoking cessation rates should be interpreted in the light of pre-event smoking prevalence. Successful quitters reported more actions to make healthy lifestyle changes as compared with persistent smokers. Successful quitters more frequently reported to attend a cardiac rehabilitation programme compared with persistent smokers. Attendance at a smoking cessation programme was less prevalent in successful quitters as compared with persistent smokers.